Effects of a forefoot strengthening protocol on explosive tasks performance and propulsion kinetics in athletes: a single-blind randomized controlled trial - Romain Tourillon; François Fourchet; Pascal Edouard; Jean-Benoît Morin (PLoS ONE, 2025)
Purpose To investigate the effects of an 8-week “periodized high-load” forefoot strengthening protocol on athlete’s metatarsophalangeal joints (MTPj) flexion torque, MTPj flexors volume, sprint acceleration, cutting, and jumping overall performance and kinetics. Methods Twenty-height highly-trained athletes were randomized into a TRAINING or control group. Following a 4-week control period, TRAINING performed an 8-week forefoot strengthening protocol (2 sessions per week) followed by a 4-week detraining period. CONTROL group athletes were asked to continue their usual activities. During weeks 1, 5, 14 and 18, we assessed MTPj flexion torque, MTPj flexors volume, maximal sprint acceleration, 90-degree cutting, vertical and horizontal jumps, and foot-ankle hops. A linear mixed model was used along with individual statistical analyses using the minimal detectable change (MDC). Results TRAINING significantly and substantially increased MTPj flexion torque and MTPj flexors volume (effect size [ES]: 1.36–1.96; p < 0.001) with 92% of athletes exceeding the MDC. Subsequently, TRAINING induced significant improvements in cutting and horizontal jumping performance (ES: 0.53–1.14; p < 0.01) with 42–67% of athletes exceeding the MDC. These gains were partly attributed to enhanced medio-lateral ground reaction force transmission during cutting and increased propulsive horizontal force production and transmission during jumping (ES: 0.38–0.57; p < 0.05). Despite no effects on overall sprint acceleration performance, vertical propulsion kinetics at maximal speed improved in TRAINING after intervention (ES: 0.87–1.19; p < 0.01). No significant differences were found between the results of the interventional and detraining period demonstrating potential long-lasting effects. Conclusion An 8-week “periodized high-load” forefoot strengthening protocol allowed to improve MTPj maximal torque and MTPj flexors volume. This strength gains led also to cutting, horizontal jump overall performance and kinetics improvement as well as greater maximal speed propulsion kinetics. MTPj strength capacity may exert a more substantial impact on performance and kinetics on horizontally and medio-lateral-oriented explosive movements than on vertically-oriented ones.